ANALYSIS OF RECORDS MANAGEMENT IN SUPPORTING ACADEMIC ADMINISTRATIVE SERVICES AT POLITEKNIK LP3I JAKARTA - Intan Risqyah Aliffah; Dias Amanda Putri; Restu Badyah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Effective records management is essential for ensuring efficient and reliable academic administrative services in higher education institutions. This study aims to examine the implementation of records management, identify the challenges encountered, and explore the strategies adopted to support academic administrative services at the Academic Administration Division of Politeknik LP3I Jakarta. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis involving three academic administrative staff members. The collected data were analyzed using the Miles and Huberman interactive model, while source triangulation was applied to ensure the credibility of the findings. The results indicate that Politeknik LP3I Jakarta implements a hybrid records management system that integrates physical records stored in filing cabinets and folders with digital records managed through HRIS, SIM, OAS, and Google Drive. Records are systematically classified using alphabetical and chronological filing systems to facilitate document retrieval. Digital records can generally be retrieved within seconds or minutes, whereas locating older physical records stored in the archive warehouse may require several days. Despite these advantages, several challenges remain, including server disruptions during peak operational periods, particularly within the OAS application, human error in data entry, data duplication during system migration, and limited physical storage capacity. The study concludes that the implementation of a structured hybrid records management system has significantly improved the efficiency and quality of academic administrative services. To further enhance organizational performance, the institution should strengthen its information technology infrastructure, enforce standardized operating procedures, improve interdepartmental coordination, and provide continuous training to enhance staff competencies in digital records management.